Relationship Of Socioeconomic Level With Caries Status In Communities In Cureh Village, Indrapuri District, Aceh Besar Regency - Liana, Intan; Andriani; Rahmati, Lina (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Economic status is the position of a person or family in society based on monthly income. The socio-economic level can affect the degree of knowledge, lifestyle, and access to health information and services. The socioeconomic level also affects the family's ability to meet the needs of food intake and healthy lifestyle habits. Several factors involved in socioeconomic is work, income and education. The initial examination of dental caries conducted by researchers on 15 people in Cureh Village found that 12 of them had high criteria, namely 5.1 and 3 d low criteria, namely 1.4. The study aimed to determine the relationship between socioeconomic level and caries status in the community of Cureh Village, Indrapuri District, Aceh Besar Regency in 2022. This research is analytical with a cross-sectional design. The population in this study is the entire Cureh village community, totalling 394 people. The research sample was determined using a random sampling technique totalling 79 people. The research was carried out in Cureh Village, Indrapuri District, Aceh Besar District on 5-10 January 2022. The instruments used in this study were questionnaires, diagnostic sets, and patient status cards. The results showed that with low income there was a high number of dental caries experienced by 32 respondents (52,45%). The results of statistical tests obtained the results of p. Value 0.001 indicates < α 0.05. Based on the results of the study, it can be concluded that there is a significant relationship between socioeconomic level (income) and dental caries. It is hoped that the community will increase knowledge by seeking information about dental health from information media such as posters, advertisements, television, magazines, and newspapers, and changing maintenance behaviour such as brushing teeth regularly and checking teeth every 6 months at the dentist or health centre and consuming nutritious and fibrous food.